2005
DOI: 10.1016/j.addbeh.2005.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of tobacco use and nicotine dependence among psychiatric patients in India

Abstract: Tobacco use among psychiatric patients in developing countries has not been well-investigated. To address this issue, we screened consecutive admissions to a major psychiatric hospital in southern India, and assessed the prevalence and correlates of tobacco use and nicotine dependence. Patients (n=988) provided information about their use of tobacco products, and participated in an interview that included the Fagerström Test for Nicotine Dependence as well as measures of other substance use. Three hundred and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
34
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 20 publications
11
34
2
Order By: Relevance
“…Our finding also points to the fact that a strong socioeconomic gradient is associated with tobacco use which had its reflection on the nicotine dependency status. A study conducted among psychiatric patients who had attended a major hospital in South India also reported of higher dependence among older and less educated patients, whereas no association was found between nicotine dependence and the specific psychiatric diagnosis represented in the study (Chandra et al, 2005). In our study, the FTND score was highest for both forms of tobacco.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Our finding also points to the fact that a strong socioeconomic gradient is associated with tobacco use which had its reflection on the nicotine dependency status. A study conducted among psychiatric patients who had attended a major hospital in South India also reported of higher dependence among older and less educated patients, whereas no association was found between nicotine dependence and the specific psychiatric diagnosis represented in the study (Chandra et al, 2005). In our study, the FTND score was highest for both forms of tobacco.…”
Section: Discussioncontrasting
confidence: 70%
“…In a country like India with diverse cultural, ethnic and demographic back ground, where smoking prevalence is high, a better understanding of nicotine dependency will add-on to more possibilities in the treatment of nicotine dependence. Though a few studies were conducted in India to estimate the nicotine dependency status of selected sub-groups (Chandra et al,2005;Jhanjee and Sethi, 2010), this study was conducted exclusively in a rural population. Though studies from rural areas have not been reported, a study conducted among 500 male students representing 5 universities in Ranchi district of India reported a FTND score of 6.7±2.22 (Sahoo and Jayant., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to western societies, in countries where smoking of women is not culturally accepted, smoking among women with mental illness is found to be similar to women in the general population (33,36,47). Although smoking rates remain lower among women with mental illness, the rate of dependence among smoker women is higher in these societies (36).…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, studies with schizophrenia patients report that cigarette use is associated to male gender (30)(31)(32)(33)(34). Smoking is also associated with male sex not only in people with schizophrenia but with other mental illnesses as well (35)(36)(37). Males have a higher smoking rate also in the general public sample (29).…”
Section: Discussionmentioning
confidence: 97%
“…Most data on this topic is derived from research conducted in western countries, except for a few studies from countries such as India (12). To the best of our knowledge, there is no research data on the prevalence of nicotine dependency in patients with schizophrenia in Sri Lanka.…”
Section: Introductionmentioning
confidence: 99%